2022
DOI: 10.3389/fbioe.2022.803218
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Disease Models for Understanding Psoriasis and Atopic Dermatitis

Abstract: Psoriasis (PS) and Atopic Dermatitis (AD) are two of the most prevalent inflammatory skin diseases. Dysregulations in the immune response are believed to play a crucial role in the pathogenesis of these conditions. Various parallels can be drawn between the two disorders, as they are both genetically mediated, and characterised by dry, scaly skin caused by abnormal proliferation of epidermal keratinocytes. The use of in vitro disease models has become an increasingly popular method to study PS and AD due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
(59 reference statements)
0
14
0
2
Order By: Relevance
“…The effects of PM 2.5 and 10 are linked to different skin diseases such as AD and allergies [ 45 , 112 ]. Several studies have demonstrated that AD skin, as well as healthy skin exposed to PM, display skin barrier disruption due to decreased expression of epidermal structural proteins such as filaggrin, E-cadherin, and cytokeratins [ 43 , 44 , 113 ]. Additionally, it is suggested that AD can be influenced by the exposure to air pollution resulting in imbalance of immune cell response and IgE production, activation of AhR/NF-κB, and the generation of ROS, and these effects can be prevented by improved air quality [ 5 , 44 , 85 ].…”
Section: Major Components Of Air Pollution Affecting Skin Appearancementioning
confidence: 99%
“…The effects of PM 2.5 and 10 are linked to different skin diseases such as AD and allergies [ 45 , 112 ]. Several studies have demonstrated that AD skin, as well as healthy skin exposed to PM, display skin barrier disruption due to decreased expression of epidermal structural proteins such as filaggrin, E-cadherin, and cytokeratins [ 43 , 44 , 113 ]. Additionally, it is suggested that AD can be influenced by the exposure to air pollution resulting in imbalance of immune cell response and IgE production, activation of AhR/NF-κB, and the generation of ROS, and these effects can be prevented by improved air quality [ 5 , 44 , 85 ].…”
Section: Major Components Of Air Pollution Affecting Skin Appearancementioning
confidence: 99%
“…A unique way to rebuild itch-related skin diseases in 3D includes the incorporation of Th1 and Th17-polarized T cells, which induced psoriasiform inflammation and keratinocyte differentiation ( van den Bogaard et al, 2014 ). For a recent review on models for understanding mostly the inflammatory side of AD and psoriasis, see ( Sarama et al, 2022 ).…”
Section: D and More Advanced Modelsmentioning
confidence: 99%
“…The different in vitro models of inflamed human skin presently available can be divided into four major classes. The 2D cell cultures are the simplest models, based on a single cell population (monolayer) or a co-culture made up of different cell types normally found in skin in vivo; these cells can be isolated from lesioned skin of patients; otherwise, human skin cell lines are subjected in vitro to the action of inflammatory cytokines [ 16 ]. In order to overcome the simplicity of these models and increase the effectiveness of the reproduced epidermal barrier, 3D models have been developed, based on the self-assembly of cells or their interaction with a scaffold, recreating in this way the three-dimensional environment found in vivo that is crucial to ensure the proper cell-to-cell, cell-to-matrix and cell-to-environment interfaces [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the simplicity of these models and increase the effectiveness of the reproduced epidermal barrier, 3D models have been developed, based on the self-assembly of cells or their interaction with a scaffold, recreating in this way the three-dimensional environment found in vivo that is crucial to ensure the proper cell-to-cell, cell-to-matrix and cell-to-environment interfaces [ 17 ]. Additionally, in this case, the disease condition is recreated using patient-derived skin cells (keratinocytes/fibroblasts) or proinflammatory molecules on healthy cells [ 16 ]. Furthermore, skin-on-a-chip is one of the latest technologies developed that, as stated by Zhang and collaborators [ 18 ], “is to culture skin tissues within a microfluidic system, which can control many physical and biochemical parameters such as medium flow, mechanical force and gradients of biochemicals, mimicking the 3D microenvironments of the natural human skin”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation